COVID-19 Patient-Reported Symptoms Using FLU-PRO Plus in a Cohort Study: Associations With Infecting Genotype, Vaccine History, and Return to Health. (7th June 2022) - Richard, Stephanie A; Epsi, Nusrat J; Lindholm, David A; Malloy, Allison M W; Maves, Ryan C; Berjohn, Catherine M; Lalani, Tahaniyat; Smith, Alfred G; Mody, Rupal M; Ganesan, Anuradha; Huprikar, Nikhil; Colombo, Rhonda E; et al.
Abstract: Background: Patient-reported outcomes of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection are an important measure of the full burden of coronavirus disease (COVID). Here, we examine how (1) infecting genotype and COVID-19 vaccination correlate with inFLUenza Patient-Reported Outcome (FLU-PRO) Plus score, including by symptom domains, and (2) FLU-PRO Plus scores predict return to usual activities and health. Methods: The ep idemiology, i mmunology, and c linical c haracteristics of pandemic infectious diseases (EPICC) study was implemented to describe the short- and long-term consequences of SARS-CoV-2 infection in a longitudinal, observational cohort. Multivariable linear regression models were run with FLU-PRO Plus scores as the outcome variable, and multivariable Cox proportional hazards models evaluated effects of FLU-PRO Plus scores on return to usual health or activities. Results: Among the 764 participants included in this analysis, 63% were 18–44 years old, 40% were female, and 51% were White. Being fully vaccinated was associated with lower total scores (β = −0.39; 95% CI, −0.57 to −0.21). The Delta variant was associated with higher total scores (β = 0.25; 95% CI, 0.05 to 0.45). Participants with higher FLU-PRO Plus scores were less likely to report returning to usual health and activities (health: hazard ratio [HR], 0.46; 95% CI, 0.37 to 0.57; activities: HR, 0.56; 95% CI, 0.47 to 0.67). Fully vaccinated participants were more likely to report returning to usual activities (HR, 1.24; 95% CI, 1.04 to 1.48). Conclusions: Full SARS-CoV-2 vaccination is associated with decreased severity of patient-reported symptoms across multiple domains, which in turn is likely to be associated with earlier return to usual activities. In addition, infection with the Delta variant was associated with higher FLU-PRO Plus scores than previous variants, even after controlling for vaccination status.